THE EFFECTIVENESS OF HERBAL INGREDIENTS TO RELIEVE BREAST ENGORGEMENT : LITERATURE REVIEW - YUSTINA DEWI ANGGRAINI; RAHAJENG SITI NUR RAHMAWATI; RIRIN INDRIANI; ENY SENDRA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
In Indonesia, the incidence of breast milk retention in postpartum mothers has increased to 10% -20% of the population of postpartum mothers. In Indonesia every year the number of breast milk sufferers in Indonesia is around 2.3 million of the total postpartum mothers. Postpartum mothers who experience breast engorgement can interfere with the breastfeeding process and if not treated immediately will result in mastitis and breast abscess. One way to deal with breast dams is by compressing herbal ingredients. The purpose of this study was to determine the effectiveness of herbal ingredients to treat breast dams. This research method is a literature study or search of previous journal articles and then adjusted to the inclusion and exclusion criteria. This study uses journal articles published in the last five years. The reviewed articles were obtained from the Google Scholar and Research Gate databases. The journal review technique uses Compare and Contrast, namely by looking for similarities and differences from the journals that have been found, then the researcher draws conclusions according to the researcher's specific goals. Results of 10 journal articles reviewed (5 cabbage compress articles, 3 aloe vera compress articles and 2 ginger compress articles). The results of the review show that there is an influence of herbal ingredients to overcome breast dams. Cabbage herbal ingredients are antibiotic, while aloe vera and ginger herbs contain active substances that are anti-inflammatory which can relieve pain and inflammation in the breasts. In conclusion, giving compresses with herbal ingredients is effective for dealing with breast dams. ABSTRAKDi Indonesia tingkat kejadian bendungan ASI pada ibu nifas naik menjadi 10%-20% dari populasi ibu nifas. Di Indonesia setiap tahun jumlah penderita bendungan ASI di Indonesia berkisar 2,3 juta dari total ibu nifas. Ibu nifas yang mengalami bendungan payudara dapat menganggu proses menyusui dan jika tidak segera ditangani akan mengakibatkan mastitis dan abses payudara. Salah satu cara untuk mengatasi bendungan payudara adalah dengan kompres bahan herbal. Tujuan penelitian ini untuk mengetahui efektivitas bahan herbal untuk mengatasi bendungan payudara. Metode penelitian ini merupakan penelitian studi literatur atau penelusuran artikel jurnal terdahulu kemudian disesuaikan dengan kriteria inklusi dan eksklusi. Penelitian ini menggunakan artikel jurnal publikasi lima tahun terakhir. Artikel yang direview diperoleh dari database Google Schoolar dan Research Gate. Teknik review jurnal menggunakan Compare dan Contrast yaitu dengan mencari suatu kesamaan dan perbedaan dari jurnal yang telah ditemukan kemudian peneliti menarik kesimpulan sesuai dengan tujuan khusus peneliti. Hasil dari 10 artikel Jurnal yang di review (5 artikel kompres kubis, 3 artikel kompres lidah buaya dan 2 artikel kompres jahe). Hasil review menunjukkan terdapat pengaruh bahan herbal untuk mengatasi bendungan payudara. Bahan herbal kubis bersifat antibiotic, sedangkan herbal lidah buaya dan jahe mengandung zat aktif yang bersifat anti inflamasi yang dapat meredakan rasa nyeri dan peradangan pada payudara. Kesimpulan pemberian kompres dengan bahan herbal efektif untuk mengatasi bendungan payudara.